Initial Trabeculectomy With Mitomycin-C for Secondary Glaucoma-associated With Uveitis in Behçet Disease Patients. Issue 7 (July 2017) - Komae, Keiko; Takamoto, Mitsuko; Tanaka, Rie; Aihara, Makoto; Ohtomo, Kazuyoshi; Okinaga, Kimiko; Matsuda, Junko; Nakahara, Hisae; Fujino, Yujiro; Kaburaki, Toshikatsu
Abstract : Purpose: To examine clinical outcomes following an initial trabeculectomy with mitomycin-C for secondary glaucoma associated with uveitis in Behçet disease (BD) patients. Design: Retrospective interventional case series. Patients and Methods: Twenty-two eyes in 18 patients with uveitic glaucoma (UG) associated with Behçet disease who underwent an initial trabeculectomy with mitomycin-C between January 1996 and August 2014 were retrospectively reviewed. The main outcome measures were intraocular pressure (IOP) control, persistence of a filtering bleb, incidence of postoperative complications, and preopertaive and postoperative frequency of uveitic attacks. We analyzed persistence rates using Kaplan-Meier life tables based on 3 definitions of target IOP control (⩽21, ⩽18, ⩽15 mm Hg) and filtering bleb persistence. Result: The persistence rates of postoperative IOP at ⩽21, ⩽18, and ⩽15 mm Hg at 5 years after surgery were 76.1%, 71.5%, and 68.1%, respectively, whereas that of a filtering bleb was 54.4%. Hypotony as a postoperative complication was observed in 4 (18.2%) cases. No significant difference was observed between the preoperative and postoperative frequency of uveitic attacks (1.36±1.15 vs. 0.95±1.49 times/y, P =0.16). There was 1 case in which recurrence of uveitis after surgery caused a loss of filtering bleb, which required a reoperation. Conclusions: At 5 years after surgery, the persistence rate of postoperative IOP control (⩽21 mm Hg) was 76.1% and that of a filtering bleb was 54.4%. The frequency of uveitis recurrence did not significantly increase after surgery. Attention must be paid to avoid such recurrence to maintain the filtering bleb.